Clinical Development of PD-1 Blockade in Hematologic Malignancies. Issue 1 (January 2018) - Pianko, Matthew J.; Goldberg, Aaron D.; Lesokhin, Alexander M.
Abstract : Abstract: Clinical development of immune checkpoint inhibitors targeting the PD-1 pathway has led to clinical benefits for patients with multiple solid tumor and hematologic malignancies and has revolutionized modern oncology. High response rates to PD-1 blockade in patients with classical Hodgkin lymphoma and certain subtypes of non-Hodgkin lymphoma highlight an intrinsic biologic sensitivity to this strategy of treatment. Despite early success of checkpoint inhibitor and immunomodulatory drug combinations in phase 2 studies in multiple myeloma, safety concerns in patients treated with the combination of immunomodulatory drugs and checkpoint inhibitors in myeloma have stalled drug development in this space. Novel combination approaches exploring PD-1 inhibitors with epigenetic modifiers in leukemia are underway.